Choreography Exploration of Sekar Lodra Dance: Concept, Process, and Presentation Form: at SMAN 8 Malang - Muhammad Rehan, Andri; Sasanadjati, Jajuk Dwi (Solah, 2025)
This study aims to explore the choreography of the Sekar Lodra dance developed at SMAN 8 Malang, focusing on its concept, creation process, and presentation form in the 2017 Student Art Creation Week (Pekan Cipta Seni Pelajar). The research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results show that the concept of this dance was inspired by the values of discipline, resilience, and grace, reflecting the character of the students at SMAN 8 Malang. The choreography creation process was carried out collaboratively between art teachers and students through stages of movement exploration, improvisation, and composition. The presentation of the Sekar Lodra dance during the 2017 Student Art Creation Week adopted a dramatic structure with a dynamic storyline, symbolic costume and makeup, and spatial arrangements that highlighted unity and the spirit of togetherness. This research is expected to contribute by helping audiences learn about local folklore or legends from the Malang area and appreciate the uniqueness of local artistic traditions.